Implementation of Itsbat Nikah as A Way To Get The Legal Power Which is not Recorded - Achmad Budi Waskito (Jurnal Daulat Hukum, 2018)
Article 2 (1) states the Marriage Act, marriage is valid if it is done according to the law of each religion and belief. Furthermore, Article 2 (2) states every marriage is recorded in accordance with the legislation in force. Thus a marriage must comply with religious law and positive law. Statements about the validity of marriages taking place before Act No. 1 of 1974 concerning marriage and run other regulations. Solutions that marriage is not recorded can be reached by way of itsbat nikah propose marriage to the Religious Courts under Article 7 Compilation of Islamic Law (KHI). According to Article 7 paragraph (1) KHI marriages under Islamic law can only be proven with Marriage Certificate made by the Registrar of Marriage Officer. On the one hand Regulation Legislation Indonesia expressed registration of marriage is the only evidence of the occurrence of marriage, but on the other side of the law provide a way out for people who can not prove their marriage with the street Determination of Marriage (Itsbat nikah). Itsbat nikah as the authority of the PA need for legal protection should be equivalent law or legal rules included in the sort order legislation.Keywords: Implementation of Itsbat nikah, Religious Courts Authority, Marriage Not Recorded.